2013
DOI: 10.1111/odi.12065
|View full text |Cite
|
Sign up to set email alerts
|

Urban legends series: oral leukoplakia

Abstract: To date, the term oral leukoplakia (OL) should be used to recognize 'predominantly white plaques of questionable risk, having excluded (other) known diseases or disorders that carry no increased risk of cancer'. In this review, we addressed four controversial topics regarding oral leukoplakias (OLs): (i) Do tobacco and alcohol cause OLs?, (ii) What percentage of OLs transform into oral squamous cell carcinoma (OSCC)?, (iii) Can we distinguish between premalignant and innocent OLs?, and (iv) Is proliferative ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
66
1
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 164 publications
3
66
1
13
Order By: Relevance
“…In 2003, a systematic review indicated that OLK had a prevalence of 0.5 to 3.4% (Petti, 2003), with a reported malignant transformation rate that ranges from 0.13 to 17.5% (Holmstrup et al, 2006). Recently, epidemiological studies revealed that the malignant transformation rate for OLK varied enormously based on Arduino's study, ranging from 0.13% to 36.4% (Arduino et al, 2013). It has been reported that the risk factors associated with the malignant transformation of OLK included gender (Napier and Speight, 2008), long duration of OLK ( Van der Waal, 2010), and location on the tongue (Zhang et al, 2001).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In 2003, a systematic review indicated that OLK had a prevalence of 0.5 to 3.4% (Petti, 2003), with a reported malignant transformation rate that ranges from 0.13 to 17.5% (Holmstrup et al, 2006). Recently, epidemiological studies revealed that the malignant transformation rate for OLK varied enormously based on Arduino's study, ranging from 0.13% to 36.4% (Arduino et al, 2013). It has been reported that the risk factors associated with the malignant transformation of OLK included gender (Napier and Speight, 2008), long duration of OLK ( Van der Waal, 2010), and location on the tongue (Zhang et al, 2001).…”
Section: Introductionmentioning
confidence: 94%
“…It has been reported that the risk factors associated with the malignant transformation of OLK included gender (Napier and Speight, 2008), long duration of OLK ( Van der Waal, 2010), and location on the tongue (Zhang et al, 2001). Besides, alcohol abuse (Goldstein et al, 2010) and chewing tobacco (Arduino et al, 2013) also have been identified to be strongly associated with OLK and OSCC. Basing on the macroscopic appearance, OLK is broadly classified into two clinical subtypes, namely homogeneous and non-homogeneous ones.…”
Section: Introductionmentioning
confidence: 97%
“…Leukoplakia is considered a clinical description, broadly categorised as homogeneous or non‐homogeneous, with no specific histopathological pattern . These chronic lesions have reported rates of malignant transformation ranging from 0.13% to 36.4% with a weighted average annual oral cancer incidence attributable to leukoplakia of 1.36% . This malignant transformation is more commonly seen in non‐homogeneous types of leukoplakia with for example a sevenfold increase reported in a Danish population .…”
Section: Introductionmentioning
confidence: 99%
“…Due to a lack of specific baseline characteristics, the PVL diagnosis is made retrospectively, based on observation of progressive clinical and microscopical characteristics of the lesions[5]. Thus, evaluation of biopsy specimens from representative areas is important in establishing the existence of epithelial dysplasia or carcinoma along with clinical evolution[15]. …”
Section: Introductionmentioning
confidence: 99%